From Tokyo to Wounded Knee: Two Afterlives of the Sunagawa Struggle. Issue 2 (3rd July 2017) - Wright, Dustin
Abstract: The Sunagawa Struggle, a massive anti-US base protest in the suburbs of western Tokyo, had lasting impacts not only on the US–Japan security alliance, but also on the people who participated on both sides of the protest lines. This article traces the lives of two people who were profoundly changed by their experiences of the anti-base movement in Japan: Dennis Banks, a young airman who was tasked with guarding the base and would later help found the American Indian Movement; and Sunagawa protestor Shimada Seisaku, who spent a career as a Tachikawa city councilperson and remained committed to anti-base activism.